Status ketersediaan fosfor dan penyerapannya oleh kedelai (Glycine max L. Merril) akibat pemberian amelioran pada ultisol warmare - Ishak Musa’ad; Alce Ilona Noya; Marce Naa; Aplena Ellen Bless (Agrotek, 2020)
The aim of this study was to determine the interaction between ameliorant andvarieties on soybean growth and P nutrient uptake in Ultisol soil at Warmare. This researchwas conducted using a randomized block design (RAK) in two factors, namely ameliorant(A) of manure as the main factor consisting of 3 levels including: A0 (without ameliorant),A1 (chicken manure) and A2 (goat manure). Soybean varieties (V) as the second factorincluded: V1 (Anjasmoro) and V2 (Wilis). The results showed that the interaction betweenameliorant and variety siginificantly affected plant height at 5 week, number of trifoliateleaves at 3 week, number of branches and nutrient uptake of P. Giving goat manureameliorant to Anjasmoro variety produced the highest plant (48.42 cm) at 5 week. Theapplication of chicken manure and goat manure to the Anjasmoro variety produced thehighest number of trifoliate leaves (5.00 pieces) at 3 week. In the variable number ofbranches, the Wilis variety which was given goat manure obtained the highest number ofbranches (5.66 branches). The highest nutrient uptake of P (9.77 g) was found in theAnjasmoro variety which was given chicken manure.